Characterization and performance evaluation of enzymes supporting material developed from Sg. Sayong clay and waste clay for tapioca saccharification process / Nurul Aini Edama - Edama, Nurul Aini (2015)
Immobilization of the enzymes on inorganic clay mineral is very useful in practical applications to overcome limitations of immobilized enzyme such as low long term stability and poor reusability of enzyme. Inorganic clay mineral proved to be an excellent supporting material for immobilization of enzymes by encapsulation technique. In this research, two types of clay material with different characteristics were evaluated for the enzyme immobilization process. The clay that used in this research was obtained from natural and palm oil processing waste clay sources. Characterization study has been done for both clay material using BET Surface Area, X-Ray Flouresence (XRF), Fourier Transform Infrared (FTIR), X-Ray Diffraction (XRD) and Field Emission Scanning Electron Microscopy (FESEM) analysis. The enzymes were encapsulated on the alg-clay beads where the alginate was used as a medium to be mixed with clay to encapsulate enzymes in the form of beads. The enzymes were successfully encapsulated within algclay beads with enzyme loading efficiency was more than 90%. The result also revealed that the highest immobilization yield was obtained at 2% (w/v) of the clay concentration for both types of clay material. From the reusability study, the results proved that immobilization of the enzymes onto the clay supporting material showed a high stability and availability for multiple uses as it could be reused up to seven cycles. The relative activity of enzyme immobilized on treated clay retained about 50% activity, meanwhile, the immobilized enzyme on untreated and waste clay retained 23% and 32% of activity respectively. Overall, the use of clay from natural and waste sources as enzymes supporting materials was successfully done in this research. Different sources and characteristic of clay could result in the different performance of tapioca saccharafication process. This method could have significant economic impact on the industrial of bioconversion of starch into glucose as it has low cost of the materials and its ability to retained the enzyme for many times and can be a good potential of enzymes supporting material in immobilization technology.